2019
DOI: 10.1128/mbio.01659-19
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid and CD4 T Cells Comprise the Latent Reservoir in Antiretroviral Therapy-Suppressed SIVmac251-Infected Macaques

Abstract: Human immunodeficiency virus (HIV) eradication or long-term suppression in the absence of antiretroviral therapy (ART) requires an understanding of all viral reservoirs that could contribute to viral rebound after ART interruption. CD4 T cells (CD4s) are recognized as the predominant reservoir in HIV type 1 (HIV-1)-infected individuals. However, macrophages are also infected by HIV-1 and simian immunodeficiency virus (SIV) during acute infection and may persist throughout ART, contributing to the size of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 86 publications
(145 reference statements)
1
81
1
Order By: Relevance
“…Additional support for macrophages as tissue reservoirs comes from studies of experimental SIV-infections of NHPs. For instance, macrophages isolated from various tissues of SIV-infected animals harbor replication competent viruses, as determined by the quantitative viral outgrowth assay (QVOA) [22,23]. Utilizing TCR beta as a marker of T cell contamination in macrophage preparations, these authors concluded that contribution of contaminated or phagocytosed infected T cells in the QVOA is negligible [22,23].…”
Section: Hiv Infection In Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional support for macrophages as tissue reservoirs comes from studies of experimental SIV-infections of NHPs. For instance, macrophages isolated from various tissues of SIV-infected animals harbor replication competent viruses, as determined by the quantitative viral outgrowth assay (QVOA) [22,23]. Utilizing TCR beta as a marker of T cell contamination in macrophage preparations, these authors concluded that contribution of contaminated or phagocytosed infected T cells in the QVOA is negligible [22,23].…”
Section: Hiv Infection In Macrophagesmentioning
confidence: 99%
“…For instance, macrophages isolated from various tissues of SIV-infected animals harbor replication competent viruses, as determined by the quantitative viral outgrowth assay (QVOA) [22,23]. Utilizing TCR beta as a marker of T cell contamination in macrophage preparations, these authors concluded that contribution of contaminated or phagocytosed infected T cells in the QVOA is negligible [22,23]. Macrophage tropic HIV-1 that can infect cells with low CD4 expression has been isolated from cerebrospinal fluid (CSF) of a patient on suppressive cART, suggesting production of HIV particles from replicating CNS reservoirs, that are most likely macrophages/microglia [24].…”
Section: Hiv Infection In Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this we formulated CCR5 targeting ARV loaded nanoformulation with the potential to block HIV entrance and promote cellular immunity against HIV infection, specifically in memory CD4+ T-cells as they commit themselves to provide antiviral immunity as latent HIV-1 reservoir (34). Alongside memory CD4+ T-cells, the myeloid lineage, such as monocytes/macrophages, are believed to be other potential HIV-1 sanctuaries (35, 36). Our hypothesis is the novel CCR5 targeted ARV nanoformulation approach could combine different strategies to ensure dual protection against HIV to the CCR5+ cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This general approach is highly versatile and should allow for a broad range of infected cell types to be examined in vivo. For example, HIV latency in the myeloid compartment is likely critical to viral persistence (35,(66)(67)(68)(69), and multiple reports suggest this compartment may respond quite differently to curative approaches, as compared to lymphoid reservoirs (70,71). It may be fruitful to inject the U1 HIV chronically-infected promonocytic cell line (72) into NSG mice to examine LRA responses in myeloid cells.…”
Section: Discussionmentioning
confidence: 99%